Analysis Of Marketing Strategy For Kenangan Coffee - Samari; Subagyo (Journal of Management, 2024)
Activities classified as business activities involve the pursuit of financial gain. Kopi Kenangan experienced the same thing. The goal of this study is to identify Kopi Kenangan's SWOT in order to maintain consumer demand for the beverage. This study used EFAS analysis, which includes a SWOT matrix to get data and identify the Kopi Kenangan quadrant's location. This study employed a descriptive qualitative methodology that made use of SWOT matrix analysis. The research subjects in this study were managers, Kopi Kenangan staff, and 35 customers in order to use Google forms to investigate current data. The data for this study was gathered through interviews and questionnaires. The study's findings indicate that Kopi Kenangan has competition from a wide range of similar businesses, but it can also benefit from its prime location in the heart of the city and its ability to provide low prices, both of which can help the company grow. It is necessary for managers to put into practice a diversification strategy, which calls on them to seize any possibilities and leverage any future advantages.